ANALISIS PRODUKTIVITAS PENGGUNAAN TENAGA KERJA PADA USAHATANI KENTANG - M. Noor Salim, Darwati Susilastuti dan Rini Setyowati (Agrisia: Jurnal Ilmu-Ilmu Pertanian, 2019)
Potato production in Indonesia is not yet optimal, influenced by many factors including the area of planting, the level of farmers' knowledge, the level of work expanse, working capital, the use of production facilities and their management. The purpose of this study was to determine the level of productivity of labor use in potato farming and to analyze the factors of production, namely the number of workers (out of work), age, education and duration of work on productivity of labor use.The study was conducted in Pangalengan Subdistrict, Bandung 2018. The number of samples was 30 potato farmers. Labor productivity is calculated based on the ratio between the amount of revenue and the amount of farmer's outflow. Data analysis with multiple linear regression. Optimizing the use of labor is calculated based on the elasticity of production, namely the ratio of the value of marginal products to labor costs.Simultaneously the amount of labor flow, age, education and length of work had a significant effect on the productivity of labor use with a contribution amount of 75.5%. Partially, the number of workers has a significant negative effect on the productivity of labor use, while age, education and length of work do not significantly affect the productivity of labor use.The optimization level of -9,589 <1, indicates that the use of labor in the study site is too much, so it is not optimal. The suggestion is that the use of labor needs to be recalculated, especially in the number of workers so that the maximum income of farmers. The need for job analysis in accordance with the stages of crop cultivation and the creation of networks within farmer groups or between farmer groups. Keywords: labor, age, education, length of work, outpouring productivity work, workforce optimization